Penggunaan Media Animasi Berbasis Macromedia Flash untuk Meningkatkan Hasil Belajar Siswa pada Konsep Materi Sistem Peredaran Darah Manusia - Situmorang, Risya Pramana; Andayani, Elisabeth Perti (Assimilation: Indonesian Journal of Biology Education, 2019)
This research aims to improve cognitive, affective and psychomotor learning outcomes through using animation based on macromedia flash. The subjects of classroom action research were 20 students, 11 male students and 9 female students from class VIII Christian Middle School 4 Salatiga. The study was conducted for 2 months in the 2017/2018 school year with 4 meetings. Measurements on cognitive learning outcomes, used instruments in the form of learning outcomes tests with 25 items, affective and psychomotor domains using questionnaire and observation sheets. Data processing and analysis used is description analysis. The percentage gain in the pre-cycle is 25% and the percentage of student learning completeness is obtained in the first cycle with a percentage of 52.9%. Furthermore cognitive learning outcomes also increased in the second cycle to 82.3%. The increase in the percentage of students 'completeness with an average of 53.4% indicates that there is a change and an increase in students' cognitive learning outcomes from the pre-cycle, cycle I and cycle IIAffective learning outcomes in the first cycle had a achievement of 55%, the acquisition of affective aspects in the first cycle still had not achieved the expected completeness, namely the standard score of 70%. However, in the second cycle the affective aspect achieved a percentage score of 78%. While the psychomotor aspects in the first cycle were 53%, increasing up to 75% in the second cycle with completeness of â‰¥75%.